Ankyloglossia, Syndactyly and Polydactyly in the Pediatric Patient - Morgado Dias, J; Baptista, A; Alegrete, N; Areias, C; Soares, H (My University, 2023)
Ankyloglossia is a congenital alteration in the development of the tongue characterized by the presence of a short or thick lingual frenulum, which leads to a limitation in its movements. There is an associative inconsistency between ankyloglossia and complications with breastfeeding, speech, swallowing, breathing, and the development of orofacial structures, and it is urgent to make more scientific research in this area. In the presence of polydactyly and syndactyly may be also present ankyloglossia. The purpose of this paper is to present two ankyloglossia cases with finger alterations, without a syndromic disease, and lead the medical team to research this topic and make an improved treatment plan for these cases.
Keywords: Criança; Anquiloglossia; Sindactilia; Polidactilia; Child; Ankyloglossia; Syndactyly; Polydactyly